PERAN ARSITEKTUR AKAR DALAM ADAPTASI SORGUM TERHADAP CEKAMAN KEKERINGAN (Review) - Mandasari, Putri A.; Suryawati, Sinar; Arrasyid, Bagus; Murniyanto, Eko (Institute of Computer Science (IOCS), 2025)
Sorghum is a drought-tolerant cereal crop and a strategic component of food security in semi-arid regions. Its adaptation to water deficit is largely determined by root system architecture (RSA), which includes root depth, lateral distribution, and interactions with microorganisms. An adaptive RSA allows sorghum to access water reserves, enhance nutrient uptake, and maintain growth and grain yield under drought. Root physiological mechanisms, such as osmolyte accumulation and antioxidant systems, support cellular homeostasis, while hormonal regulation (abscisic acid) and the transcription factor SbNAC9 coordinate gene expression for root development and stress defense. The synergy among these morphological, physiological, and molecular responses enables sorghum to sustain metabolism during prolonged water deficits. This review synthesizes existing literature on the role of RSA in sorghum’s drought adaptation, highlighting the connections between root structure, physiological responses, and molecular pathways. These insights provide a valuable framework for root-based breeding strategies aimed at enhancing drought tolerance. Ultimately, RSA acts as a central hub, integrating various adaptations to support crop resilience and productivity under arid conditions.